Resistance Exercise Training-Induced Muscle Hypertrophy Was Associated with Reduction of Inflammatory Markers in Elderly Women - Kishiko Ogawa; Kiyoshi Sanada; Shuichi Machida; Mitsuharu Okutsu; Katsuhiko Suzuki (Hindawi Limited, 2010)
Aging is associated with low-grade inflammation. The benefits of regular exercise for the elderly are well established, whereas less is known about the impact of low-intensity resistance exercise on low-grade inflammation in the elderly. Twenty-one elderly women (mean age ± SD, 85.0 ± 4.5 years) participated in 12 weeks of resistance exercise training. Muscle thickness and circulating levels of C-reactive protein (CRP), serum amyloid A (SAA), heat shock protein (HSP)70, tumor necrosis factor (TNF)-α, interleukin (IL)-1, IL-6, monocyte chemotactic protein (MCP-1), insulin, insulin-like growth factor (IGF)-I, and vascular endothelial growth factor (VEGF) were measured before and after the exercise training. Training reduced the circulating levels of CRP, SAA (P<.05), HSP70, IGF-I, and insulin (P<.01). The training-induced reductions in CRP and TNF-α were significantly (P<.01, P<.05) associated with increased muscle thickness (r=−0.61, r=−0.54), respectively. None of the results were significant after applying a Bonferroni correction. Resistance training may assist in maintaining or improving muscle volume and reducing low-grade inflammation.